Effect of Community Based Program on the Knowledge, Treatment Adherence and Quality of Life of Hypertensive Adults Through Precede Proceed Model - Sughra Majeed, Muhammad Afzal, Kabir Ozigi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypertension has consistently been a leading cause of morbidity and mortality in different countries and has continuously increased in prevalence. Although hypertension is manageable with lifestyle modification and anti‐hypertensive medications, inadequate knowledge poor adherence to treatment regimens and poor quality of life are issues that have led to poor blood pressure control. Objectives: To assess the effect of a community‐based health programme grounded on the Precede‐Proceed model, on the knowledge, treatment adherence and quality of life of adults with hypertension Study Design: Quasi‐experimental, one‐group pretest–post‐test design. Methodology: The Precede‐Proceed model was used to develop and evaluate the effect of the community‐based health programme. A total of 50 community‐dwelling adults with hypertension participated in the programme which included blood pressure monitoring targeted health educations, and individualized lifestyle modification plans. Knowledge, treatment adherence and quality of life were assessed at the start and at the end of the 3‐month programme. Gathered data were analyzed using descriptive statistics and paired t-test. Practical Implications: This research suggests that a community-based health program, grounded in the Precede-Proceed model, can effectively improve the knowledge and treatment adherence of hypertensive adults, as well as their overall quality of life. This program can serve as a community approach to managing hypertension, which is a prevalent and leading cause of morbidity and mortality in many countries. However, the study highlights the need for additional interventions to improve the general physical health domain of quality of life in hypertensive adults. Results: After 3 months, the mean score of knowledge level, treatment adherence and quality of life were significantly improved, attributing more than 45% of the change. Although knowledge scores were significantly higher after the education programme, but it only accounted small change in general physical domain of quality of life. Conclusion: Although the health education programme made significant and large improvements in the knowledge of hypertension and adherence scores of adult patients with hypertension, it only accounted small increment on the general physical health domain of quality of life among hypertensive adults. The community‐based health programme was effective and can be considered as a community approach to improving knowledge, treatment adherence and quality of life of patients with hypertension in the community setting. Keywords: Knowledge, Treatment Adherence, Quality of Life, Precede‐Proceed Model, Health Education, Community, Adults